The unusual bifunctional catalysis of epimerization and desaturation by carbapenem synthase. - Topf, M; Sandala, G; Smith, D; Schofield, C; Easton, C; Radom, L (2004)
High-level ab initio calculations have been used to study the mechanism for the conversion of (3S,5S)-carbapenam to the biologically active beta-lactam antibiotic, (5R)-carbapenem, catalyzed by carbapenem synthase. This process involves epimerization at C5 and desaturation at C2/C3. Our calculations suggest that the reaction proceeds via initial abstraction of the C5 hydrogen atom, followed by epimerization. In addition, we have identified an attractive mechanism for coupling the epimerization and desaturation in thermodynamically favorable steps with the aid of an external reductant. Other mechanisms that have been examined have significantly higher energy requirements or do not appear to be consistent with available experimental evidence.